Mobile Assisted Language Learning in Intensive English Course for Freshmen Year Students - Mandala Putra, Made Agus; Santosa, Made Hery (Universitas Pendidikan Ganesha, 2020)
Learning on twenty first century has influenced the use of technology especially as contextual learning media in the classroom. Moreover, digital generation students have already known the role of technology and have adapted it successfully. Therefore, it was very important to introduce attractive and active learning by using authentic activities and one of these activities was called Mobile Assisted Language Learning (MALL). This learning brought the world’s information only to the students’ smart phone. In contrast to traditional learning in the classroom, the students did not fully gain knowledge in the classroom. In fact, the implementation of MALL could give students’ freedom to learn in terms of time and place. The result of this research showed that students had obstacles in learning especially in terms of activities and the used of teaching media. Students needed authentic learning media that could improve their four skills.